Homo-Tandem Polymer Solar Cells with VOC1.8 V for Efficient PV-Driven Water Splitting - Neophytou, Marios; Beaujuge, Pierre M.; Hamid, Mahmoud Abdul; Gao, Yangqin; Gaïtis, Alexandre; Takanabe, Kazuhiro; Le Corre, Vincent M. (My University, 2016)
High-voltage tandem and triple-junction polymer solar cells (PSCs) were demonstrated by using one of the highest- V OC, high-efficiency polymer donors in bulk heterojunction (BHJs) with fullerenes, namely poly(benzo[1,2- b :4,5- b'] dithiophene?thieno[3,4- c ]pyrrole-4,6-dione) (PBDTTPD). While the efficiency of PBDTTPD-based single-junction PSCs is limited by incomplete optical absorption, we show that homo-tandem PSCs with MoO3 /ultrathin Al/ZnO intermediate recombination layers can achieve higher PCE values. The PV performance of single-junction PBDTTPD:PC 71 BM PSCs were investigated with the standard device structure ITO/PEDOT:PSS/PBDTTPD:PC71 BM/Ca/Al. Next, the potential for further PCE increments were examined via a triple-junction PSC device approach, using the same ZnO/Al/MoO3 interconnection layer between the three subcells. PBDTTPD homo-tandem PSCs yield high operating voltages of 1.54 V at their maximum power point, providing sufficient potential for the dissociation of water and the evolution of hydrogen and oxygen in a standard electrochemical cell.
Keywords: bulk heterojunction solar cells; homo‐tandem; multijunction devices; organic photovoltaics; PCBM; PV‐driven water splitting